Inventário e quantificação dos geossítios cársticos do Parque Estadual Intervales (SP) - Camargo, Túlio César Rocha (2018)
The increase in public use in natural areas in the last decades is characterized by the interest of knowing and contemplating the natural patrimony, constituted by elements of bio and geodiversity - the latter being the focus of this research. One of the representative elements of geodiversity is classified as geosite. In karstic terrain, caves are common examples of geosites, as long as they have some dimension of intrinsic value or even of use for science, conservation, tourism, or education. In this context the objective of this research was to analyze the karstic geosites of the State Park Intervales (SPI), making possible their quantification and valuation. The methods used were based on bibliographical research and field work to identify, characterize, inventory and evaluate selected geosites, whether or not open to public use, outside and inside of this Natural Protected Area (NPA). The main results demonstrated the categorization of each geosite from its values: intrinsic, scientific, tourist, use / management and educational, which was the new dimension of analysis. Through the synthesis of these values, the results of the quantification were applied in equations to measure the categories of geosites for each type of use: scientific, tourism and proposed tourist-educational. In the end, it was calculated and compared the Ranking of Traditional Relevance (TR) and Ranking of Proposed Relevance (PR) of each geosite, revealing that some caves have a high tourist value, due to the large number of visits and activity carried out with elementary schools, high school, undergraduate and postgraduate, a considerable scientific value in the representativeness of geological processes, variety of elements of bio and geodiversity as well as a high educational value. It is concluded that the inventory and quantification of geosites can serve as a tool for the expansion of strategies for geoconservation, through activities that correspond to the characteristics of each geosite, both at the regional and national levels. Considering that educational tourism and speleotourism are already activities developed in and around the SPI and a source of income for the local communities, it is also expected that the work will disseminate the geotourism potential of the area, based on a future strategy of geotourism and geoconservation.